PENTINGNYA INTERAKSI SOSIAL DALAM MENCIPTAKAN MANAJEMEN KELAS YANG EFEKTIF PADA SISWA KELAS X IPA 1 DI MAN 1 SERANG - Yuniar, Euis Ismayati; Kangiden, Farida Ariyani; Trikawati; Maesaroh; Nurjaman (JEDLISH : Journal Of Education and English Language Teaching, 2025)
This study aims to identify strategies and patterns of interaction between teachers and students in class X IPA 1 of State Islamic Senior High School (MAN) 1 Serang. In the context of classroom management, interaction is not only about conveying information, but also includes how teachers build relationships, provide feedback, facilitate discussions, enforce rules and respond to individual student needs. Good teacher and student interaction in the teaching and learning process can certainly create a conducive classroom atmosphere. Therefore, interaction between teachers and students is a crucial aspect in creating an effective learning environment. In this study, using descriptive qualitative methods, data were collected through observation, in-depth interviews, and documentation. The results showed that in effective classroom management, supported by adequate physical facilities and the implementation of 9 classroom management practices by teachers, including checking student readiness, enforcing rules, motivation, and providing feedback. The implications of this study highlight the importance of balancing order and an empathetic approach in classroom management, as well as the need for more inclusive interaction strategies to support students' motivation and development holistically. So social interaction with the teacher's communication style has the potential to help students achieve high grades in the lessons they take, including friendly, attentive, relaxed, and dramatic styles